Preparation and Characterization of Photo-Curable PCL/PEG-Diacrylate for Additive Manufacturing Tissue Engineering Scaffold Application - Cheng, Yih-Lin (2016)
PCL is one of important tissue engineering scaffold materials. Besides traditional scaffold fabrication methods, additive manufacturing (AM) techniques have also been used to provide controlled pore size and required geometry. Most AM approaches utilize extrusion or sintering to generate PCL scaffolds, yet few use photo-curing. In this research, photo-curable PCL (PCL-DA) was considered as the scaffold material, which will be photo-polymerized by visible light using a self-developed dynamic masking AM system. In order to improve its strength and hydrophilic character, PEG-diacrylate (PEG-DA) is added in the material system. Three different ratios (6:4, 7:3, 8:2) of PCL-DA to PEG-DA were prepared and characterized by differential scanning calorimetry (DSC), thermomechanical analyzer (TMA), tensile tests, water contact angles, and cell culturing. The results showed that the ratio of 6:4 is the best among the three. A preliminary study of scaffold fabrication was conducted by the AM system to demonstrate the feasibility of adopting photo-curable PCL/PEG-DA for tissue engineering scaffold application.